MINOM-Portugal in Portuguese contemporary museology (Cadernos de Sociomuseologia, 2022)
The MINOM – International Movement for a New Museology is, in Portugal, an example of associative longevity, of critical mass aggregation and of inspiring reflection for museum practice and museological theory.It is a critical Movement with a social base and territorial impact, reasoned on the relationship with Social Museology and Sociomuseology, which are part of its basic philosophy and characteristics.In a process of self-criticism and in an attempt to overcome the immobility of the Portuguese associative movement, MINOM-Portugal recently defined its action strategies to accompany the 21st century social changes and the consequent adaptation needs of museology and museums.Key words: Social Museology; sociomuseology; associativism